The Future of Transhumants' Sustainable Resource Use in Bhutan: Pressures and Policies - Namgay, Kuenga; Millar, Joanne E.; Black, Rosemary S. (Frontiers in Sustainable Food Systems, 2021)
Cattle and yaks in Bhutan are mainly managed in transhumance system, grazing common pool resources. This is, however, changing due mainly to policy changes and development pressure. The unequal land policies now restrict mobility for cattle based transhumance by agro-pastoralists while it is expected to remain same for the yak based pastoralists. Essential public infrastructures too are being built in the common pool resources thus reducing the grazing areas for cattle and yaks alike. This study used empirical & administrative data and policy documents to understand the forces that increasingly contribute towards halting transhumance and see how it might change the grazing landscape and socialscape in the future. The study found grazing in future will likely transform from extensive to semi-intensive system but with smaller herd sizes for cattle based agro-pastoralists. This is being achieved through interventions implemented by livestock department; promoting crossbreeding with European dairy breeds. Transhumant herder turned sedentary smallholder farmers are fast adopting sedentary lifestyle. Yak based transhumance, however, is expected to continue with improvements in product development, packaging, branding and market access. The yak transhumance will thrive partly because it is necessary to be domiciled in the highlands practicing yak herding to get access to cordyceps. The government rule allows only residents of highlands to collect the most highly priced caterpillar fungus, Cordyceps sinensis, which is available only in some of the highlands. This is changing not only the landscapes, from grazing in large expanse of forest and open meadows, to restricted semi-intensively managed smallholder farms, with possible impact on biodiversity. Crossbreds of European dairy cattle are fast replacing indigenous siri cattle of Bos indicus type. The socialscapes is fast changing with both highlanders as well as mid and lowland herders. They now have access to television and mobile phones. Many of these places inhabited by herders are now connected, at least, by a dirt road. This means their travel time to nearest health facilities or shops are shortened from days to hours.